Oligoarticular Hemarthroses and Osteomyelitis Complicating Pasteurella Meningitis in an Infant - Charles Nathan Nessle; Allison K. Black; Justin Farge; Victoria A. Statler (MDPI AG, 2017)
A 5-month-old previously healthy female presented with a one-week history of fever and increased fussiness. Her presentation revealed an ill-appearing infant with an exam and cerebrospinal fluid (CSF) studies concerning bacterial meningitis; CSF cultures grew Pasteurella multocida. Additionally, brain magnetic resonance imaging (MRI) demonstrated cervical osteomyelitis. Despite multiple days of antibiotic therapy, she remained febrile with continued pain; MRI showed oligoarticular effusions, and aspiration of these joints yielded bloody aspirates. Evaluations for coagulopathy and immune complex-mediated arthropathy were negative. The patient improved following appropriate antibiotic therapy and spontaneous resolution of hemarthroses, and was discharged to a short-term rehabilitation hospital. P. multocida is a small, encapsulated coccobacillus that is part of the commensal oral flora of animals. It most commonly causes skin infections in humans, yet is a rare cause of meningitis in the pediatric population, especially in children <1 year of age. Transmission due to P. multocida is most commonly due to direct contact with animals. To our knowledge, this is the first case of oligoarticular hemarthroses and cervical osteomyelitis complicating P multocida meningitis. This case highlights the physician's potential for cognitive bias and premature anchoring, and the resulting implications in delivering excellent patient care.